Developing targets for radiation transport experiments at the Omega laser facility. (13th July 2017) - Capelli, D.; Charsley-Groffman, C.A.; Randolph, R.B.; Schmidt, D.W.; Cardenas, T.; Fierro, F.; Rivera, G.; Hamilton, C.; Hager, J.D.; Johns, H. M.; Lanier, N. E.; Kline, J.L.
Abstract : Targets have been developed to measure supersonic radiation transport in aerogel foams using absorption spectroscopy. The target consists of an aerogel foam uniformly doped with either titanium or scandium inserted into an undoped aerogel foam package. This creates a localized doped foam region to provide spatial resolution for the measurement. Development and characterization of the foams is a key challenge in addition to machining and assembling the two foams so they mate without gaps. The foam package is inserted into a beryllium sleeve and mounted on a gold hohlraum. The target is mounted to a holder created using additive manufacturing and mounted on a stalk. The manufacturing of the components, along with assembly and metrology of the target are described here.